Diversity and nesting ecology of Indo-Malayan stingless bees (Hymenoptera: Apidae) in Aceh Province, Indonesia - MUHAMMAD FARHAN PUTRA EMIL; WINDRA PRIAWANDIPUTRA; SIH KAHONO; TRI ATMOWIDI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Emil MFP, Priawandiputra W, Kahono S, Atmowidi T. 2024. Diversity and nesting ecology of Indo-Malayan stingless bees (Hymenoptera: Apidae) in Aceh Province, Indonesia. Biodiversitas 25: 3617-3627. The study of stingless bee diversity and nest ecology is needed as an integral part of beneficial insects. Information on stingless bees in the northern peninsula of Sumatra, Indonesia was limited. The study aimed to analyze the species richness and nest ecology of Indo-Malayan stingless bees in Aceh Province. Through exploratory surveys, data were collected from two observation sites, i.e., Aceh Besar and Bener Meriah Districts, between July and August 2023. Results showed that ten species of stingless bees were recorded. The stingless bees' body lengths ranged from 4.6 to 11.7 mm, and forewing lengths from 3 to 8.8 mm. Stingless bee nest substrates were found on natural substrates and those associated with settlements. Nest entrances varied in size (1.75-13.54 cm in length, 0.65-7.57 cm in horizontal diameter, 0.45-7.46 cm in vertical diameter), with long pipe funnel with dim gray, cavity shapes dominantly circular and irregular, soft textures with resin and pores. These nests were located 1-300 m from water sources in elevation ranges 0-600 cm. The cells in the stingless bee nest were composed of brood cells, honey cells, pollen cells, and stone layers. Variations in the nest entrance funnel may related to the adaptability to the environment and internal factors.